2015
DOI: 10.3389/fgene.2015.00116
|View full text |Cite
|
Sign up to set email alerts
|

Global impact of KRAS mutation patterns in FOLFOX treated metastatic colorectal cancer

Abstract: Background: Colorectal cancer (CRC) is one of the most frequent events in oncology. Advances in molecular understanding of the processes of carcinogenesis have shed light on the fundamental mechanisms of tumorigenesis. Currently, knowledge of the molecular basis of its pathogenesis is being used to improve patient care and devise more rational therapeutics. Still, the role played by the mutation patterns of mutated genes in the clinical outcomes that patients on pharmacological treatment receive remains unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…The prevalence of KRAS mutations differs amongst human tumors. Previous studies have shown that the frequency of mutation is around 30–40% in CRC and we reported 32% of mutations [20]. These observations are similar when comparing different ethnic groups [18,21,22].…”
Section: Somatic Genomics In Oncologysupporting
confidence: 88%
“…The prevalence of KRAS mutations differs amongst human tumors. Previous studies have shown that the frequency of mutation is around 30–40% in CRC and we reported 32% of mutations [20]. These observations are similar when comparing different ethnic groups [18,21,22].…”
Section: Somatic Genomics In Oncologysupporting
confidence: 88%
“…In patients with advanced CRC who are treated with folinic acid, fluorouracil, and oxaliplatin (FOLFOX), the standard first-line therapy for CRC, KRAS mutation is predictive of inferior response and this overall effect is driven largely by those cancers expressing G12D [35]. Consistent with the observation that patients with G12V mutations do better than those with other codon 12 mutations in terms of overall survival [27], late stage lung cancers expressing G12V appear to respond better to platinum-based chemotherapy than do cancers expressing other KRAS alleles [36].…”
Section: Kras Mutational Status As a Predictive Factormentioning
confidence: 99%
“…Specifically, mutations within KRAS lead to the constitutive activation of the EGFR signaling pathway,3 and the cumulative survival rate of patients with wild-type KRAS is significantly higher than that of patients with mutations in this gene. A previous study has showed that the survival rate of patients with the wild-type KRAS gene receiving EGFR antibody therapy was significantly higher than that of patients harboring mutants 4. Moreover, a large phase III clinical study has showed that the codons 12 and 13 of exon 2 of the KRAS gene correlate with blocked EGFR gene monoclonal antibody status with cetuximab and panitumumab and that patients with wild-type KRAS benefit the most from EGFR antibody therapy 5…”
Section: Introductionmentioning
confidence: 99%